Health condition, income loss, food insecurity and other social inequities among migrants and refugees during the COVID-19 pandemic in Brazil - Heriederson Sávio Dias Moura; Thaís Zamboni Berra; Rander Junior Rosa; Ruan Víctor dos Santos Silva; Débora de Almeida Soares; Juliana Soares Tenório de Araújo; Fernanda Bruzadelli Paulino Costa; Rosa Maria Pinheiro de Souza; Murilo César do Nascimento; Titilade Kehinde Ayandeyi Teibo; Maria Del Pilar Serrano-Gallardo; Ricardo Alexandre Arcêncio (BMC, 2023)
Abstract Background Brazil is the destination of many international migrants and refugees and, given the circumstances of their entry into the country, many face difficulties due to the absence of targeted policies. Thus, the objective of this study was to survey the social impact of COVID-19 on international migrants and refugees regarding income loss, food insecurity and other social inequities, and to identify explanatory factors on these aspects. Methods This is a cross-sectional, analytical study. We used a validated instrument applied by trained interviewers. Descriptive analysis and binary logistic regression were performed to identify factors associated with income loss and food insecurity. Results A total of 360 individuals from sub-Saharan African and South American countries participated in the study. Individuals who were white, black/brown, yellow, had an occupation/employment, and earned less than one minimum wage were more likely to lose income. Those who reported no income, received less than one minimum wage, and were diagnosed with COVID-19 were more likely to be food insecure. Conclusions The study advances knowledge by identifying factors associated with income loss, food insecurity, and individuals' difficulty in accessing health services and social support measures in Brazil.